Analysis of Transient Phenomena Due to a Direct Lightning Strike on a Wind Energy System - João P. S. Catalão; Rafael B. Rodrigues; Victor M. F. Mendes (Energies, 2012)
This paper is concerned with the protection of wind energy systems against the direct effects of lightning. As wind power generation undergoes rapid growth, lightning damages involving wind turbines have come to be regarded as a serious problem. Nevertheless, very few studies exist yet in Portugal regarding lightning protection of wind energy systems using numerical codes. A new case study is presented in this paper, based on a wind turbine with an interconnecting transformer, for the analysis of transient phenomena due to a direct lightning strike to the blade. Comprehensive simulation results are provided by using models of the Restructured Version of the Electro-Magnetic Transients Program (EMTP), and conclusions are duly drawn.